ANALYSIS OF INITIAL SUPPORT DESIGN OF SAMARINDA TUNNEL STA 0+425 USING LATTICE GIRDER WITH 3D MODELING - Anugrah Krista, Shela
Samarinda Tunnel is a tunnel with a horseshoe geometric shape that has a height of 10.5 m and a width of 12.8 m. This tunnel will be excavated by top heading and bench excavation with excavation progress of 3 m each progress. This tunnel has a length of 400 m with the deepest depth of 62 m from ground level. Therefore, a proper initial support system is needed to avoid the risk of collapse. The initial support system was derived from recommendations based on rock classification according to Terzaghi, RMR, and Q-System. Of the three recommendations, a combination was carried out to determine the support to be applied to the tunnel. Based on the results of the analysis, it was found that the initial support of the Samarinda tunnel consisted of lattice girder P150-25-30 with a space of 1.5 m, shotcrete K225 20 cm thick, and added reinforcement in the form of a rockbolt with a diameter of 25 mm with a length of 4 m and circumferential and longitudinal spaces along 2 m and 1.5 m. This is based on the results of the analysis which shows the formation of arch effect around the tunnel, vertical strain value of 0.09% and convergent strain of 0.04%, displacement value less than 10 cm, and SF value of shotcrete support and lattice girder from empirical and numerical calculations of more than 1.5.